Pengaruh Pengajian Rutin Malam Jum'at terhadap Perubahan Perilaku Masyarakat di Desa Pasar Maga - Elismayanti Rambe; Salwa Nabilah (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to analyze the level of public participation, identify behavioral changes, and examine the influence of routine Friday night Islamic learning gatherings (pengajian) on behavioral changes among the community in Pasar Maga Village using a quantitative approach with descriptive analysis and simple linear regression. The results indicate that the level of community participation falls into the high category, with an average score of 39.23, demonstrating a transformation of religious activities from mere ceremonial routines into essential spiritual and social needs. In line with these findings, behavioral changes following participation in the routine gatherings showed a significantly positive trend, with an average score of 39.45, where the internalisation of religious values was proven to enhance worship discipline, communication ethics, and social initiatives. Furthermore, simple linear regression analysis empirically confirms a positive and significant influence of the routine Friday night gatherings on community behavioral changes in Pasar Maga Village. Although the contribution of the routine gathering variable accounts for 12.8%—with the remaining 87.2% influenced by external factors such as family environment, formal education, social media, and social interaction—this non-formal religious activity is empirically proven to be an effective and strategic agent of moral change in shaping better community character